Penanaman nilai agama Islam pada siswa melalui kegiatan pondok ramadhan di MTs Almaarif 03 Singosari - Primrose, Ailsa Tsabita; Imani, Raniah Oktariza; Rajabi, Elfina Sabilia; Syehan, Billy; Islami, Ronadhia Nabilatus; Rohmana, Wahyu Indah Mala (Maliki Interdisciplinary Journal, 2024)
This study aims to explore the methods of instilling Islamic religious values in students through the Pondok Ramadhan activities at MTs Almaarif 03 Singosari. These activities involve a series of religious events specifically designed for the month of Ramadan, including Qur'an recitation, congregational prayers, religious lectures, and Islamic discussions. Using a qualitative approach with observations and interviews, this research found that the Pondok Ramadhan activities are effective in deepening students' understanding of Islamic teachings, enhancing personal piety, and shaping a strong religious character. The results indicate that integrating religious activities into the school curriculum can be an effective strategy for instilling religious values in students, strengthening the school's community bonds, and improving the overall quality of religious education.